2020
DOI: 10.31729/jnma.4941
|View full text |Cite
|
Sign up to set email alerts
|

Preparedness for Coronavirus Disease in Hospitals of Nepal: A Nationwide Survey

Abstract: Introduction: Coronavirus disease pandemic has affected large number of peopleglobally and has continued to spread. Preparedness of individual nations and the hospitals isimportant to effectively deal with the surge of cases. We aimed to obtain nation wide data fromNepal, about hospital preparedness for COVID-19. Methods: Online questionnaire was prepared in accordance with the Center for Disease Controlrecommendations to assess preparedness of hospitals for COVID-19. The questionnaire wascirculated to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 5 publications
0
16
0
Order By: Relevance
“…Only half of respondents from a Jordanian survey reported access to institutional protocols to deal with COVID19 cases [ 16 ]. Less than 40% of respondents from a study carried out in Nepal reported a policy to receive suspected or proven cases with COVID19 [ 17 ]. Most respondents had been trained on donning and doffing PPE and felt comfortable doing it.…”
Section: Discussionmentioning
confidence: 99%
“…Only half of respondents from a Jordanian survey reported access to institutional protocols to deal with COVID19 cases [ 16 ]. Less than 40% of respondents from a study carried out in Nepal reported a policy to receive suspected or proven cases with COVID19 [ 17 ]. Most respondents had been trained on donning and doffing PPE and felt comfortable doing it.…”
Section: Discussionmentioning
confidence: 99%
“…However, ICU equipment and trained personnel are scarce. 12 It is difficult to procure essential ICU equipment and personal protective devices as medical manufacturing facilities are non-existent in the country. The government, as well as private institutions, have already spent enormous sums developing new makeshift intensive care units and procuring consumables; it is doubtful whether most of these institutions can fund the additional cost of running optimal services in the operating rooms (ORs) and intensive care units.…”
Section: Discussionmentioning
confidence: 99%
“…Nepal represents a real scenario of low-and middleincome countries (LMICs) where pandemic mitigation efforts are impacted largely by the lack of medical supplies and infrastructure. This includes personal protective equipment (PPE) and ventilators, the limitation of well-trained manpower, the unavailability of enough diagnostic kits; a lack of a proper coordination mechanisms among stakeholders, and poor reporting and documentation of cases (41)(42)(43)(44). This pandemic has taught Nepal that it should invest more in research and development in the public health sector, besides the current primary focus on curative medicine.…”
Section: Discussionmentioning
confidence: 99%